(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This paper presents an automatic pattern grading technique by obtaining point grading rules automatically in order to avoid the manual input of cardinal point increments in the traditional GCAD system. Based on the principles of the pattern grading and pattern structures, patterns are divided into two categories: basic patterns and fashion patterns that are derived from basic patterns. Since basic patterns and fashion patterns are the specific form of 2D garment structure of human body, the grading rule of the former has relationship with that of the latter quantitatively, thus the fashion patterns can be graded automatically by applying the grade rule data of basic patterns. This paper depicts the computer class design scheme of the technique, including the construction of the pattern data structure, the acquirement of the grading rules of basic patterns by parameterization, the algorithms on the automatic transformation from the grading point increment of basic patterns to the one of fashion patterns and the application of grading rule of basic pattern in fashion patterns. The experiment results show that the technique is feasible.